Outcome measures in the clinical evaluation of ambulatory Charcot-Marie-Tooth 1A subjects - Mori, Laura; Prada, Valeria; Signori, Alessio; Pareyson, Davide; Piscosquito, Giuseppe; Padua, Luca; Pazzaglia, Costanza; Fabrizi, Gian Maria; Smania, Nicola; Picelli, Alessandro; Schenone, Angelo (European journal of physical and rehabilitation medicine, 2019)
The outcome measures (OMs) in clinical trials for Charcot-Marie-Tooth disease (CMT) still represent an issue. A recent study highlighted that three additional clinical OMs, the 10-Meter Walk Test (10MWT), the 9-Hole Peg Test, and foot dorsal flexion dynamometry, further improve discrimination between severely and mildly affected patients. Another study has recently assessed the validity and reliability of the 6-Minute Walk Test (6MWT). The aim of this study was to identify the most useful scales in the clinical evaluation of CMT1A patients. Observational study of the baseline data collected in a multicenter, prospective, randomized, single blind, controlled study to evaluate the efficacy and safety of an innovative rehabilitation protocol based on treadmill training, stretching, respiratory, and proprioceptive exercises (TreSPE study) in CMT1A patients. The outpatient service of the four Italian centers involved, which are specialized in hereditary neuropathies. Fifty-three subjects with a clinical and genetically confirmed diagnosis of CMT1A. At baseline, in addition to the CMT Neuropathy Score, all subjects underwent walking evaluation (6MWT, 10MWT), balance assessment (Berg Balance Scale [BBS], Short Physical Performance Battery [SPPB]) and a subjective evaluation of quality of life (SF36) and walking ability (Walk12). Analyzing the baseline data, as expected, we found a strong correlation between walk and balance evaluation, proving the validity of these tests in investigating the functional impairment of CMT1A subjects. Particularly, we found that subjects with better balance control walk at higher speed and perceive less limitations in their physical activities or motor skills. This can be reconducted to the fact that ankle stability depends upon different factors such as anatomy integrity, muscle strength and proprioception. We identify the 6MWT, 10MWT, and SPPB as the most useful scales, in addition to the CMTNS, to evaluate the functional impairment of CMT1A patients who retain their walking capability and we suggest the use of SPPB because of its rapidity to assess balance and gait disorders in clinical settings. In the clinical practice it is important to evaluate patients comprehensively but rapidly. These outcome measures can help us to correctly assess balance and walking ability in CMT1A patients.